2009
DOI: 10.1016/j.juro.2009.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Erectile Function by Antioxidant Therapy in Diabetic Rats

Abstract: To our knowledge this is the first report that tempol and insulin can restore erectile function in diabetic rats by inhibiting apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 21 publications
0
31
0
1
Order By: Relevance
“…26 Additional studies have shown the potential use of ROS scavengers in salvaging erectile function in diabetic condition. 27,28 In corpora cavernosa from streptozotocin-induced diabetic rats, antioxidant treatment improves superoxide dismutase activity, increases endothelial nitric oxide synthase expression, and reduces ROS generation in corpora cavernosa, followed by an improvement in intracavernosal pressure/mean arterial pressure ratio. 29 Despite the evidence that DM is an important risk factor for ED, little is known about IPA function in diabetic conditions, and even less is known about the involvement of any catalytic core subunit of NOX, such as NOX1, in IPA function in DM.…”
mentioning
confidence: 99%
“…26 Additional studies have shown the potential use of ROS scavengers in salvaging erectile function in diabetic condition. 27,28 In corpora cavernosa from streptozotocin-induced diabetic rats, antioxidant treatment improves superoxide dismutase activity, increases endothelial nitric oxide synthase expression, and reduces ROS generation in corpora cavernosa, followed by an improvement in intracavernosal pressure/mean arterial pressure ratio. 29 Despite the evidence that DM is an important risk factor for ED, little is known about IPA function in diabetic conditions, and even less is known about the involvement of any catalytic core subunit of NOX, such as NOX1, in IPA function in DM.…”
mentioning
confidence: 99%
“…Experimentally-induced diabetic models are well-established to elaborate the mechanism of diabetic-induced ED and also a recommended model for establishing the beneficial effect of any new compound against diabetes ED [9]. In present study, sever sexual impairment was found in STZ-induced diabetic rat by inhibiting the EL, PEI, ML and IL latencies and increasing the MF and IF frequencies.…”
Section: Resultsmentioning
confidence: 48%
“…The superoxide dismutase (SOD) is also a vital enzyme that eradicates the superoxide radicals. However, increased production of ROS can inhibit SOD activity, which augment the peroxynitrite and ameliorate NO levels [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has been presented verifying that DM also has a tight correlation with the apoptosis of various cell types, including the cavernous smooth muscle cells [40], corpus cavernosal endothelial cell [10]. Apoptosis is a basic programmed cell death process to maintain the dynamic balance of the cell environment.…”
Section: Discussionmentioning
confidence: 99%